Distribusi Musiman Nitrat dan Fosfat serta Pemodelan Klorofil-a sebagai Indikator Ekologis Keberlanjutan Budidaya Kappaphycus alvarezii di Pulau Tarakan - Jimmy Cahyadi; Slamet Budi Prayitno; Desrina Desrina; Frida Purwanti (Jurnal Kelautan Tropis, 2025)
Seaweed farming needs essential nutrients for growth. Nitrate and phosphate are essential nutrients for the growth of seaweed algae and phytoplankton produce chlorophyll-a. Chlorophyll-a content is needed in the photosynthesis process and triggers seaweed metabolism to absorb more nutrients. This study describes the relationship between nitrate, phosphate, chlorophyll-a for west and east monsoon waters with other water quality parameters in Tarakan Island. Insitu and exsitu measurements of water quality samples at 14 stations were determined by stratified random sampling in March 2024 for the west monsoon and June 2024 for the east monsoon. The distribution of chlorophyll-a was obtained from observations of the JAXA GCOM-C OCEAN CHLA V3 satellite image and the ocean contour model from BIG. There are significant differences in the distribution of chlorophyll-a, phosphate, and nitrate in the west and east monsoons. Chlorophyll-a distribution in the west monsoon of 0.60-1.10 mg/m3 tends to be higher than that in the east monsoon of 0.50-0.85 mg/m3 divergent pattern and correlates with nitrate, phosphate, water brightness, turbidity, sea surface temperature, current and pH. Water quality in the east and west monsoons supports seaweed farming.